Solid polymer electrolyte membrane and preparation method and application thereof

By compositeing polyallyl acetoacetate and lithium salt on the porous cellulose membrane, the prepared solid polymer electrolyte membrane solves the problems of low lithium ion conductivity and lithium dendrites, improving the electrochemical performance and safety of lithium metal batteries.

CN120341354APending Publication Date: 2025-07-18JILIN DONGCHI NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311030520.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing polymer electrolyte membrane has low lithium ion conductivity and cannot meet the practical application requirements of solid electrolytes. Moreover, lithium dendrites are easily generated on the surface of lithium metal negative electrodes, which lead to safety hazards.

Method used

A porous cellulose film is used as a supporting film, composited with polyacetyl acetate, loaded with lithium salt, and prepared solid polymer electrolyte membrane through ultraviolet photopolymerization to improve flexibility and ionic conductivity.

Benefits of technology

The prepared solid polymer electrolyte membrane has high room temperature lithium ion conductivity and lithium ion migration number, which improves the electrochemical performance and safety of the battery and realizes the stability of the lithium metal negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120341354A_ABST
    Figure CN120341354A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion and lithium metal solid-state batteries, and particularly relates to a solid-state polymer electrolyte membrane as well as a preparation method and application thereof. The solid polymer electrolyte membrane provided by the invention comprises a porous cellulose membrane as well as poly (allyl acetoacetate) and lithium salt which are loaded on the surface and in pores of the porous cellulose membrane. According to the invention, the poly (allyl acetoacetate) has high ionic conductivity, the cellulose membrane with a porous structure is used as a solid electrolyte support membrane and is compounded with the poly (allyl acetoacetate) to prepare the solid polymer electrolyte membrane, and the pores and the surface of the cellulose membrane are filled with the poly (allyl acetoacetate); the flexibility of the solid polymer electrolyte membrane is improved, so that the solid polymer electrolyte membrane has high room-temperature lithium ion conductivity and lithium ion transference number.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion and lithium-metal solid-state batteries, and particularly relates to a solid polymer electrolyte membrane, a preparation method thereof, and an application thereof. Background Art

[0002] Lithium secondary batteries have been widely used in various energy storage fields such as portable electronic devices, electric vehicles, and energy storage power stations. Lithium metal anodes have advantages such as high specific capacity, low discharge potential, and light weight, and are an ideal choice for developing high-energy-density lithium secondary batteries. However, the high reactivity of lithium metal makes its compatibility with conventional electrolytes poor, so lithium dendrites are likely to be generated on the surface of the lithium metal anode, resulting in internal short circuit of the battery and causing safety problems such as combustion and explosion. In addition, liquid electrolytes also have the risks of leakage and flammability. Replacing conventional liquid electrolytes with solid electrolytes is an effective means to solve the above problems.

[0003] Compared with inorganic solid electrolytes, polymer electrolytes have advantages such as easy processing and excellent contact performance with electrode interfaces. Polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, and polyvinylidene fluoride-hexafluoropropylene copolymer are all commonly used polymer electrolytes, but the lithium-ion conductivities of these polymer electrolytes are usually low (<10 -4 S·cm -1 ), which cannot meet the actual application requirements of solid electrolytes. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a solid polymer electrolyte membrane, a preparation method thereof, and an application thereof. The solid polymer electrolyte membrane provided by the present invention has excellent flexibility, high ionic conductivity, and lithium-ion transference number, and the all-solid-state battery assembled with it has excellent electrochemical performance.

[0005] The present invention provides a solid polymer electrolyte membrane, which includes a porous cellulose membrane and polyallyl acetoacetate and a lithium salt loaded on the surface and pores of the porous cellulose membrane.

[0006] Preferably, the thickness of the solid polymer electrolyte membrane is 35-100 μm, the porosity is 30-50%, and the specific surface area is 5-7 m 2 / g.

[0007] Preferably, the mass ratio of polyallyl acetoacetate to the lithium salt in the solid polymer electrolyte membrane is (50-80):(15-45).

[0008] Preferably, the lithium salt includes one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and lithium bis(oxalato)borate.

[0009] The present invention also provides a method for preparing the solid polymer electrolyte membrane described in the above technical solution, comprising the following steps:

[0010] A mixed material liquid obtained by mixing allyl acetoacetate monomer, a UV initiator, a crosslinking agent and a lithium salt is coated on a porous cellulose membrane, and after UV polymerization reaction, it is dried to obtain a solid polymer electrolyte membrane.

[0011] Preferably, the UV initiator includes one or more of 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, ethyl 2,4,6-trimethylbenzoyl phenylphosphinate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-propanone and ethyl 4-dimethylaminobenzoate.

[0012] Preferably, the crosslinking agent includes one or more of polyethylene glycol diacrylate, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-isopropylimidazole, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, triethylenetetramine, dimethylaminopropylamine, diethylaminopropylamine, diethylenetriamine and benzoyl peroxide.

[0013] Preferably, the wavelength of the UV used in the UV polymerization reaction is 365 nm, and the irradiation time of the UV is 5 - 15 min.

[0014] Preferably, the coating is doctor blade coating or dip coating.

[0015] The present invention also provides the application of the solid polymer electrolyte membrane described in the above technical solution or the solid polymer electrolyte membrane prepared by the preparation method described in the above technical solution in a lithium-ion and lithium-metal solid-state battery.

[0016] The present invention provides a solid polymer electrolyte membrane, which includes a porous cellulose membrane and polyallyl acetoacetate and a lithium salt loaded on the surface and pores of the porous cellulose membrane. The present invention uses a cellulose membrane with a porous structure as a solid electrolyte support membrane, and is compounded with polyallyl acetoacetate to form a solid polymer electrolyte membrane. Polyallyl acetoacetate has high ionic conductivity and fills the pores and surface of the cellulose membrane, improving the flexibility of the solid polymer electrolyte membrane, and making it have high room-temperature lithium-ion conductivity and lithium-ion transference number. The results of the examples show that the room-temperature lithium-ion conductivity of the solid polymer electrolyte membrane prepared by the present invention is 1.21×10 -4 S·cm -1 , the lithium-ion transference number is 0.81, and the specific capacity of the full cell assembled with this solid polymer electrolyte membrane, a lithium metal negative electrode and a lithium iron phosphate positive electrode remains at 154 mA·h·g at 0.1 C -1 , and the lithium-lithium symmetric battery can stably cycle for 1500 h with an overpotential of about 0.017 V.

[0017] The present invention also provides a method for preparing the solid polymer electrolyte membrane, which has a simple process and is easy to operate. Description of the Drawings

[0018] Figure 1 It is a photograph of the solid polymer electrolyte membrane prepared in Example 1 of the present invention;

[0019] Figure 2 It is a SEM image of the surface of the solid polymer electrolyte membrane prepared in Example 1 of the present invention;

[0020] Figure 3 It is a SEM image of the cross-section of the solid polymer electrolyte membrane prepared in Example 1 of the present invention;

[0021] Figure 4 It is an impedance diagram of the solid polymer electrolyte membrane prepared in Example 1 of the present invention;

[0022] Figure 5 It is a chronoamperometry curve of the solid polymer electrolyte membrane prepared in Example 1 of the present invention;

[0023] Figure 6 It is a cycle curve of the lithium-lithium battery assembled with the solid polymer electrolyte membrane in Application Example 1 of the present invention;

[0024] Figure 7 It is a SEM image of the lithium negative electrode after 1500 h of cycling of the lithium-lithium battery assembled with the solid polymer electrolyte membrane in Application Example 1 of the present invention;

[0025] Figure 8 It is a rate performance curve of the lithium iron phosphate full battery assembled with the solid polymer electrolyte membrane in Application Example 2 of the present invention;

[0026] Figure 9 It is a cycle curve of the liquid lithium-lithium battery in Comparative Application Example 1 of the present invention. Detailed Embodiments

[0027] The present invention provides a solid polymer electrolyte membrane, which comprises a porous cellulose membrane and polyallyl acetoacetate and a lithium salt loaded on the surface and pores of the porous cellulose membrane.

[0028] The solid polymer electrolyte membrane provided by the present invention comprises a porous cellulose membrane. In the present invention, the thickness of the porous cellulose membrane is preferably 10-35 μm, more preferably 34 μm; the porosity of the porous cellulose membrane is preferably 68-73%, more preferably 70%; the specific surface area of the porous cellulose membrane is preferably 5-7 m 2 / g, more preferably 5 m 2 / g; the porous cellulose membrane is a commercially available product.

[0029] The solid polymer electrolyte membrane provided by the present invention comprises allyl polyacetoacetate and a lithium salt loaded on the surface and pores of the porous cellulose membrane. In the present invention, the molecular weight of the allyl polyacetoacetate is preferably 100 to 500, more preferably 142; the lithium salt preferably comprises one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate and lithium bis(oxalato)borate, and more preferably lithium bis(trifluoromethanesulfonyl)imide.

[0030] In the present invention, the thickness of the solid polymer electrolyte membrane is preferably 35 to 100 μm, more preferably 35 to 50 μm, the porosity is preferably 30 to 50%, more preferably 40%, and the specific surface area is preferably 5 to 7 m 2 / g, more preferably 5 m 2 / g; the mass ratio of allyl polyacetoacetate to the lithium salt in the solid polymer electrolyte membrane is preferably (50 to 80):(15 to 45), more preferably (60 to 75):(20 to 40). In the present invention, the role of the lithium salt is to achieve ion transport in the electrolyte.

[0031] In the present invention, allyl polyacetoacetate has high ionic conductivity, but its self-formed film has poor mechanical properties and a relatively thick film (>100 μm). The present invention uses a porous cellulose membrane as a solid electrolyte support membrane and composites it with allyl polyacetoacetate to form a solid polymer electrolyte membrane. The allyl polyacetoacetate is filled in the pores and on the surface of the cellulose membrane, improving the flexibility of the solid polymer electrolyte membrane and endowing it with high room-temperature lithium-ion conductivity and lithium-ion transference number.

[0032] The present invention also provides a preparation method of the solid polymer electrolyte membrane described in the above technical solution, comprising the following steps:

[0033] Coat the mixed material liquid obtained by mixing allyl acetoacetate monomer, a UV initiator, a crosslinking agent and a lithium salt onto the porous cellulose membrane, carry out a UV polymerization reaction, and then dry to obtain the solid polymer electrolyte membrane.

[0034] Unless otherwise specified, the present invention has no special requirements for the sources of the raw materials used in the preparation, and commercially available products well-known to those skilled in the art can be used.

[0035] The present invention mixes allyl acetoacetate monomer, a UV initiator, a crosslinking agent and a lithium salt to obtain a mixed material liquid.

[0036] In the present invention, the ultraviolet light initiator preferably includes one or more of 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, ethyl 2,4,6-trimethylbenzoyl phenylphosphinate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-propanone, and ethyl 4-dimethylaminobenzoate, and more preferably 1-hydroxy-cyclohexyl-phenyl ketone.

[0037] In the present invention, the crosslinking agent preferably includes one or more of polyethylene glycol diacrylate, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-isopropylimidazole, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, triethylenetetramine, dimethylaminopropylamine, diethylaminopropylamine, diethylenetriamine, and benzoyl peroxide, and more preferably polyethylene glycol diacrylate.

[0038] In the present invention, the mass ratio of the allyl acetoacetate monomer to the ultraviolet light initiator is preferably (50 - 70):(1 - 9), and more preferably (60 - 65):(2 - 8); the mass ratio of the allyl acetoacetate monomer to the crosslinking agent is preferably (50 - 70):(3 - 9), and more preferably (50 - 55):(5.5 - 9); the mass ratio of the allyl acetoacetate monomer to the lithium salt is preferably (50 - 70):(15 - 45), and more preferably (60 - 65):(22 - 44).

[0039] In the present invention, the mixing is preferably carried out at room temperature; the mixing is preferably stirring or ball milling, and more preferably stirring; the rate of the stirring is preferably 100 - 200 r / min, and more preferably 100 - 150 r / min; the time of the stirring is preferably 2 - 12 h, and more preferably 5 - 10 h; the rate of the ball milling is preferably 100 - 200 r / min, and more preferably 100 - 150 r / min; the time of the ball milling is preferably 2 - 12 h, and more preferably 5 - 10 h.

[0040] After obtaining the mixed material liquid, in the present invention, the mixed material liquid is coated on a cellulose membrane for ultraviolet light polymerization reaction.

[0041] In the present invention, the coating is preferably blade coating or dip coating, and more preferably blade coating; the thickness of the blade used for the blade coating is preferably 60 - 120 μm, and more preferably 60 - 90 μm.

[0042] In the present invention, the wavelength of the ultraviolet light used for the ultraviolet light polymerization reaction is preferably 365 nm, and the irradiation time of the ultraviolet light is preferably 5 - 15 min, and more preferably 5 - 10 min.

[0043] After the ultraviolet photopolymerization reaction, the present invention dries the composite film obtained from the ultraviolet photopolymerization reaction to obtain a solid electrolyte film.

[0044] In the present invention, the drying is preferably vacuum drying; the drying temperature is preferably 60-120°C, more preferably 60-100°C; the drying time is preferably 12-24 h, more preferably 16-24 h; the vacuum degree of the vacuum drying is preferably 130-135 Pa, more preferably 133 Pa.

[0045] The present invention also provides the application of the solid polymer electrolyte film described in the above technical solution or the solid polymer electrolyte film prepared by the preparation method described in the above technical solution in lithium-ion and lithium-metal solid-state batteries.

[0046] The present invention has no special limitation on the application of the solid polymer electrolyte film in lithium-ion and lithium-metal solid-state batteries, and the well-known application methods in the art can be adopted.

[0047] In the application example of the present invention, the lithium-metal solid-state battery includes a positive electrode sheet, a negative electrode, and the solid polymer electrolyte film described in the above technical solution. The positive electrode sheet is lithium iron phosphate, carbon black, and polyvinylidene fluoride with a mass ratio of 8:1:1. The negative electrode is a lithium-metal negative electrode, and the lithium-metal solid-state battery is a button-type full battery.

[0048] Next, the technical solutions in the present invention will be clearly and completely described in conjunction with the examples in the present invention, but they cannot be understood as limiting the protection scope of the present invention.

[0049] Example 1

[0050] A mixture of 0.35 g of 1-hydroxy-cyclohexyl-phenyl ketone, 0.73 g of polyethylene glycol diacrylate, 3.2 g of lithium bis(trifluoromethanesulfonyl)imide, and 5 mL of allyl acetoacetate was stirred at a rate of 100 r / min at room temperature for 5 h. The obtained mixture was coated on both sides of a cellulose film with a thickness of 34 μm using a doctor blade with a thickness of 60 μm, and then placed under an ultraviolet lamp and irradiated at a wavelength of 365 nm for 5 min for a polymerization reaction. Then, it was placed in a vacuum oven at 60°C and a vacuum degree of 133 Pa and dried for 24 h to obtain a solid polymer electrolyte film with a thickness of 42.4 μm.

[0051] Example 2

[0052] A mixture of 0.71 g of 1-hydroxy-cyclohexyl-phenylmethanone, 0.84 g of polyethylene glycol diacrylate, 3.2 g of lithium bis(trifluoromethanesulfonyl)imide and 5 mL of allyl acetoacetate was stirred at a rate of 100 r / min at room temperature for 5 h. The obtained mixture was coated on both sides of a cellulose membrane with a thickness of 34 μm using a doctor blade with a thickness of 90 μm, and then placed under an ultraviolet lamp and irradiated at a wavelength of 365 nm for 5 min for polymerization reaction. Then it was put into a vacuum oven at 80 °C with a vacuum degree of 133 Pa and dried for 24 h to obtain a solid polymer electrolyte membrane with a thickness of 35 μm.

[0053] Example 3

[0054] A mixture of 0.35 g of 1-hydroxy-cyclohexyl-phenylmethanone, 0.73 g of polyethylene glycol diacrylate, 3.4 g of lithium bis(trifluoromethanesulfonyl)imide and 5 mL of allyl acetoacetate was stirred at a rate of 100 r / min at room temperature for 5 h. The obtained mixture was coated on both sides of a cellulose membrane with a thickness of 34 μm using a doctor blade with a thickness of 120 μm, and the coating thickness was 90 μm. Then it was placed under an ultraviolet lamp and irradiated at a wavelength of 365 nm for 5 min for polymerization reaction. Then it was put into a vacuum oven at 80 °C with a vacuum degree of 133 Pa and dried for 24 h to obtain a solid polymer electrolyte membrane with a thickness of 41 μm.

[0055] Application Example 1

[0056] The solid polymer electrolyte membrane prepared in Example 1 was assembled with lithium metal into a lithium-lithium pair battery.

[0057] Application Example 2

[0058] A positive electrode sheet was prepared by mixing lithium iron phosphate, carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1; then, using lithium metal as the negative electrode, it was assembled with the solid polymer electrolyte membrane prepared in Example 1 into a lithium iron phosphate button full cell.

[0059] Application Example 3

[0060] Using lithium iron phosphate as the positive electrode, a lithium sheet as the negative electrode, and the solid polymer electrolyte membrane prepared in Example 2 as the electrolyte membrane, a lithium iron phosphate button battery was assembled.

[0061] Comparative Application Example 1

[0062] Using a cellulose membrane with a thickness of 34 μm as the separator and a mixed solution of lithium bis(trifluoromethanesulfonyl)imide and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide as the electrolyte, a liquid lithium-lithium pair battery was assembled. It was used to compare the stability of the solid electrolyte and the liquid electrolyte to the lithium metal negative electrode.

[0063] Performance Test

[0064] (1) Figure 1 Photograph of the solid polymer electrolyte membrane prepared in Example 1. It can be seen from Figure 1 that the morphology of the solid polymer electrolyte membrane prepared in Example 1 is uniform and bendable, showing flexibility.

[0065] (2) The surface and cross-section of the solid polymer electrolyte membrane prepared in Example 1 were tested by scanning electron microscopy, and the results are shown in Figure 2 and Figure 3 respectively. It can be seen from Figure 2 and Figure 3 that the polymer electrolyte has been uniformly filled into the pores of the cellulose membrane, and the surface of the electrolyte membrane is smooth, which is beneficial to the close contact between the solid electrolyte and the electrode, reducing the interfacial resistance. The thickness of the electrolyte membrane is about 42.4 μm.

[0066] (3) The room-temperature impedance of the solid polymer electrolyte membrane prepared in Example 1 was tested, and the results are shown in Figure 4 .

[0067] It can be seen from Figure 4 that through calculation, the room-temperature ionic conductivity of the solid polymer electrolyte membrane prepared in Example 1 is 1.21×10 -4 S·cm -1 .

[0068] (4) The chronoamperometry of the solid polymer electrolyte membrane prepared in Example 1 was tested, and the results are shown in Figure 5 .

[0069] It can be seen from Figure 5 that through calculation, the lithium ion transference number of the solid polymer electrolyte membrane prepared in Example 1 at room temperature is 0.81.

[0070] (5) The cycling performance of the lithium-lithium symmetric battery assembled with the solid polymer electrolyte membrane in Application Example 1 was tested, and the results are shown in Figure 6 .

[0071] It can be seen from Figure 6 that the lithium-lithium symmetric battery assembled with the solid polymer electrolyte membrane in Application Example 1 can stably cycle for 1500 h, and the overpotential is still less than 0.017 V, indicating that the solid polymer electrolyte membrane prepared by the present invention can form a stable interface with the lithium negative electrode, and it has extremely high electrochemical stability with metallic lithium.

[0072] (6) The lithium negative electrode of the lithium-lithium symmetric battery assembled with the solid polymer electrolyte membrane in Application Example 1 after 1500 h of cycling was scanned by electron microscopy, and the results are shown in Figure 7 .

[0073] As shown in Figure 7As shown, after 1500 h of cycling, the surface of the lithium metal electrode remains flat and dense, indicating that the solid polymer electrolyte membrane of the present invention is beneficial to the uniform deposition of lithium.

[0074] (7) The rate performance of the lithium iron phosphate full cell assembled with the solid polymer electrolyte membrane prepared in Application Example 2 was tested, and the results are as Figure 8 shown.

[0075] It can be seen from Figure 8 that the discharge specific capacities at 0.1C, 0.2C, 0.5C and 1C are 150 mA·h·g -1 , 146 mA·h·g -1 , 139 mA·h·g -1 , 129 mA·h·g -1 respectively. When the current returns to 0.1C, the specific capacity can recover to the initial level and can continue to cycle stably, proving that the solid polymer electrolyte membrane prepared by the present invention has excellent electrochemical stability and can be applied in full cells.

[0076] (9) The cycle performance of the liquid lithium-lithium pair cell prepared in Comparative Application Example 1 was tested, and the results are as Figure 9 shown.

[0077] It can be seen from Figure 9 that the overpotential of the liquid lithium-lithium pair cell gradually increases during cycling, and the cell short-circuits after 200 cycles, indicating that the liquid electrolyte is not conducive to the formation of a stable lithium / electrolyte interface. Comparative Application Example 1 proves the effective role of the solid polymer electrolyte prepared in this example in stabilizing the lithium / electrolyte interface.

[0078] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention rather than all of them. People can also obtain other embodiments according to this embodiment without creative work, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A solid polymer electrolyte membrane, characterized in that, It includes a porous cellulose membrane, and allyl polyacetoacetate and a lithium salt loaded on the surface and pores of the porous cellulose membrane.

2. The solid polymer electrolyte membrane according to claim 1, wherein The thickness of the solid polymer electrolyte membrane is 35 to 100 μm, the porosity is 30 to 50%, and the specific surface area is 5 to 7 m 2 / g.

3. The solid polymer electrolyte membrane according to claim 1 or 2, characterized in that, In the solid polymer electrolyte membrane, the mass ratio of allyl polyacetoacetate to the lithium salt is (50-80):(15-45).

4. The solid polymer electrolyte membrane according to claim 1, characterized in that, The lithium salt includes one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and lithium bis(oxalato)borate.

5. The method for preparing the solid polymer electrolyte membrane according to any one of claims 1 to 4, comprising the following steps: Coat a mixed material liquid obtained by mixing an allyl acetoacetate monomer, a UV initiator, a crosslinking agent, and a lithium salt onto a porous cellulose membrane, carry out a UV polymerization reaction, and then dry to obtain a solid polymer electrolyte membrane.

6. The preparation method according to claim 5, characterized in that, The UV initiator includes one or more of 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, ethyl 2,4,6-trimethylbenzoyl phenylphosphinate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, and ethyl 4-dimethylaminobenzoate.

7. The preparation method according to claim 5, characterized in that, The crosslinking agent includes one or more of polyethylene glycol diacrylate, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-isopropylimidazole, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, triethylenetetramine, dimethylaminopropylamine, diethylaminopropylamine, diethylenetriamine, and benzoyl peroxide.

8. The preparation method according to claim 5 or 6, characterized in that The wavelength of the UV used in the UV polymerization reaction is 365 nm, and the irradiation time of the UV is 5-15 min.

9. The preparation method according to claim 5, wherein The coating is knife coating or dip coating.

10. The application of the solid polymer electrolyte membrane according to any one of claims 1 to 4 or the solid polymer electrolyte membrane prepared by the preparation method according to any one of claims 5 to 9 in a lithium-ion and lithium-metal solid battery.

Citation Information

Patent Citations

  • Ketone group-containing solid polymer electrolyte and battery

    CN113224382A

  • Manufacturing process of gel electrolyte battery

    CN115117439A

  • Polymer electrolyte and lithium-ion battery including the polymer electrolyte

    US20220216513A1